Automatic Disambiguation of Author Names: Foundations, Methods and Open Issues - Ferreira, Anderson A.; Laender, Alberto H. F. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2023)
This tutorial is based on our book “Automatic Disambiguation of Author Names in Bibliographic Repositories” and aims to spread the problem and its challenges among the SBBD community. Author name ambiguity problem occurs when an author publishes works under distinct names or distinct authors publish works under similar names. This problem may be caused by a number of reasons, including the lack of standards and common practices, and the decentralized generation of bibliographic content. In this tutorial, we intend to present an ample view on the automatic disambiguation of author names. We start by discussing its motivational issues, defining the author name disambiguation task and presenting its foundations. Next, we describe some methods proposed by our research group, as well as some recent approaches to author name disambiguation. Finally, we discuss open issues.